2019
DOI: 10.1016/j.redox.2019.101268
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic uptake and release of SOD3 from intracellular stores in macrophages modulates the inflammatory response

Abstract: Superoxide dismutase 3 (SOD3) is an extracellular enzyme with the capacity to modulate extracellular redox conditions by catalyzing the dismutation of superoxide to hydrogen peroxide. In addition to synthesis and release of this extracellular protein via the secretory pathway, several studies have shown that the protein also localizes to intracellular compartments in neutrophils and macrophages. Here we show that human macrophages release SOD3 from an intracellular compartment within 30 min following LPS stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…SOD3 is known as a predominant form of SODs in plasma [ 10 ]. In many studies, it has been shown that SOD3 is mainly expressed in endothelial cells [ 11 , 26 , 27 ], and its decrease was associated with vascular endothelium damage and the infiltration of inflammatory cells [ 5 , 10 , 28 ]. In our previous study [ 29 ], we demonstrated an increased concentration of endothelium damage markers in AP patients which could be associated with decreased SOD3 concentration in the plasma of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SOD3 is known as a predominant form of SODs in plasma [ 10 ]. In many studies, it has been shown that SOD3 is mainly expressed in endothelial cells [ 11 , 26 , 27 ], and its decrease was associated with vascular endothelium damage and the infiltration of inflammatory cells [ 5 , 10 , 28 ]. In our previous study [ 29 ], we demonstrated an increased concentration of endothelium damage markers in AP patients which could be associated with decreased SOD3 concentration in the plasma of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…SOD3 is the extracellular superoxide dismutase which has unique characteristics and functions in the cellular signal transduction [ 1 , 10 ]. Recent studies have also shown that SOD3 can be localized in intracellular compartments in neutrophils and macrophages [ 11 ]. It is highly expressed in certain tissues, such as cardiovascular endothelium, placenta and lung, and moderately within kidney, pancreas and uterus, cartilage, skeletal muscle, adipose tissue, brain and eye [ 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This release is accompanied by a reduced level of superoxide in the extracellular space and hence modulated redox conditions [ 57 , 59 ]. Macrophages can internalize recombinant SOD3 for storage, implicating a sorting step for deviation from the archetypical endosomal traffic to lysosomes [ 60 ]. In contrast to neutrophils that establish secretory vesicles by bulk membrane endocytosis, the uptake of SOD3 in macrophages appears to be mediated by the specific interaction with the cell surface receptor, low-density lipoprotein receptor-related protein 1 (LRP1), which is highly expressed in macrophages [ 60 , 61 ].…”
Section: Sod3 Is Contained In Agonist-regulated Vesicles In Macropmentioning
confidence: 99%
“…Macrophages can internalize recombinant SOD3 for storage, implicating a sorting step for deviation from the archetypical endosomal traffic to lysosomes [ 60 ]. In contrast to neutrophils that establish secretory vesicles by bulk membrane endocytosis, the uptake of SOD3 in macrophages appears to be mediated by the specific interaction with the cell surface receptor, low-density lipoprotein receptor-related protein 1 (LRP1), which is highly expressed in macrophages [ 60 , 61 ]. Agonist-induced release of SOD3 from macrophages increases both the level of the enzyme in the extracellular environment and on the cell surface within hours [ 60 ].…”
Section: Sod3 Is Contained In Agonist-regulated Vesicles In Macropmentioning
confidence: 99%